PENERAPAN STATISTIK TERAPAN DALAM PENDIDIKAN: ANALISIS HUBUNGAN ANTARA GAYA MENGAJAR GURU DAN INTERAKSI KELAS TERHADAP HASIL BELAJAR SISWA SMA NEGERI 2 SUNGAI LILIN (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between teaching styles and classroom interaction on students' learning outcomes at SMA Negeri 2 Sungai Lilin. The research employed a quantitative approach with a correlational design. The sample consisted of 72 students selected using purposive sampling techniques. Data were collected through teaching style questionnaires, classroom interaction questionnaires, and students' academic records. Data analysis used descriptive and inferential statistics, including Pearson correlation and multiple linear regression. The results show that: (1) there is a positive and significant relationship between teaching style and learning outcomes; (2) classroom interaction is positively and significantly related to learning outcomes; and (3) teaching style and classroom interaction simultaneously have a significant effect on learning outcomes, contributing 62%. These findings indicate that learning quality is strongly influenced by pedagogical strategies and classroom interaction dynamics.